IMPLEMENTATION OF HUMAN RIGHTS PARAMETERS IN THE ESTABLISHMENT OF REGIONAL REGULATIONS IN TOBA SAMOSIR REGENCY - Yuli Rosdiana (NOMOI Law Review, 2021)
The importance of guidance for human rights material as the reference in regulating and limiting human rights in legislation, especially Regional Regulation is the values of human rights to be realized by the involvement and intervention of government/local governments in the form of regulations. The research method used in this writing is normative legal research method with empirical data. The main data in this research is secondary data. There are 3 (three) Regulations of the Regency of Toba Samosir that optimally accommodate the parameters of human rights in making the Regional Regulation. However, there is 1 (one) Regional Regulation that has 2 (two) indicators of parameters of human rights that have yet to be fulfilled. Suggestively, the Government to make a special regulation related to The Parameters of Human Rights in Regional Regulation Making that will be guidance for Provincial/Regency/Municipal Governments in making their Regional Regulations, so that they will be more measured in viewing Human Rights and it is also suggested for the Government of Regency of Toba Samosir in accommodating implemented parameters of human rights in making the Regional Regulations by involving the Regional Office of the Ministry of Law and Human Rights both in the harmonization, discussion and finalization of conception of the Draft Regional Regulation.Keywords: Parameters, Human Rights, Regional Regulation.